The Notion of Justice as a Philosophical-Legal Mythologem - F. P. Furman (Теоретическая и прикладная юриспруденция)
In the article the problematics of formation of legal values, formed in different historical stages and in different states, but having both general regularities and the features conditioned by the level of socio-political, economic, spiritualcultural, moral development, development of democratic institutions of power, civil society and the rule of law are considered. The complex understanding of the process of formation of legal life and legal field in society and state is generalized and formulated. We analyze the existing approaches to the understanding of the process of legal regulation and their evaluation in the general system of legal values through the prism of such philosophical and legal phenomenon as justice.